Physiological responses of the brown mussel Perna perna (Mollusca, Bivalvia) exposed to the anionic surfactant linear alkylbenzene sulphonate (LAS). - Stefanoni, Marina Freitas; Abessa, Denis Moledo de Souza [UNESP] (My University, 2011)
The effects of the Linear Alkylbenzene Sulphonate (LAS) were evaluated on the mussel Perna perna, using physiological and genotoxic biomarkers. The Micronuclei (MN) assay was used to estimate effects at nuclear level, whereas the physiological effects were evaluated by measuring the oxygen consumption and ammonia excretion rates. Significant effects were observed for the MN assay and the ammonia excretion rate, even in low concentrations. The oxygen consumption was not affected in the tested concentrations. For MN and ammonia excretion, the animals exposed to intermediate concentrations were not affected, but responded to the higher concentrations, indicating the existence of compensatory mechanisms at physiological level. However, parallel to this study other authors indicate the presence of progressive effects at the cellular level, suggesting that the organisms are not capable to recover of such increasing effects. Additionally, the results show that the levels of LAS observed for Brazilian coastal waters may chronically affect the biota.